Dimensi Eskatologi dalam Laudato Si’ dan Implikasinya terhadap Tanggung Jawab Ekologis dalam Iman Kristiani - Sergius Lay; Yohanes Jok Pendopo Laoli; Ester Fosumange Laia; Rosalia Gulo; Fendirianus Harefa; Mersianis Laia (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2026)
This study examines the eschatological. Dimensions present in the encyclical Laudato Si’ and their implications for ecological responsibility within the Christian faith. The increasing global ecological crisis necessitates a serious theological reflection capable of grounding believers’ engagement with environmental issues in their faith convictions. Eschatology, as the doctrinal framework concerning ultimate realities, addresses not merely the end of individual human existence but, more profoundly, the hope for the renewal and transformation of all creation in God. The research employs a qualitative method with a library research approach, drawing primarily on ecclesiastical documents, Sacred Scripture, and relevant theological literature. The findings demonstrate that Laudato Si’ integrates a robust eschatological vision, wherein the promise of “a new heaven and a new earth” constitutes the theological foundation for human responsibility toward creation. Contrary to interpretations that treat eschatological hope as a rationale for passivity or disengagement from the world, Laudato Si’ affirms that such hope actively motivates believers to participate in the care and preservation of the environment as an integral expression of their faith calling. This study concludes that eschatology possesses genuine practical relevance for everyday Christian life, particularly in cultivating ecological awareness. Faith in the ultimate fulfillment of God’s salvific plan, far from diminishing present-day responsibilities, intensifies the moral obligation to treat the earth as a “common home” entrusted to humanity.